Час поверхневої концентрації стоку для дощів постійної інтенсивності та лінійних басейнів стоку - Жук, В. (Видавництво Національного університету “Львівська політехніка”, 2005)
The main time parameter which one influences very strongly on the stormwater discharge is the time of surface runoff concentration. In the paper are obtained analytical and numerical expressions for calculating the surface concentration time for rains with the constant intensity for linear watersheds.
Keywords: 628.29